Comportamiento de componentes agronómicos y de rendimiento bajo dosis creciente de gallinaza en Cucumis melo L., var. "melón gaucho redondo" en Zungarococha-Loreto.2021 - Ramirez Lopez, Axel Giordano (2022)
The experiment was developed in the Workshop of Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at Km. 3.5 of the road to Quistococha -Llanchama, south of the city of Iquitos, whose geographical coordinates are: South Latitude 03º 46 ? 13.2 ? ?; West Longitude 73º 22 ? 10.4´´; Altitude: 126 masl. The type of research was quantitative, experimental, explanatory, transversal and prospective, with an independent variable (Chicken dose) and eight dependent variables (Number of fruits/plant, Number of fruits/plot, length of the fruit, diameter, thickness of the bark of the fruit, weight of fruit, weight of fruits/plant and weight of fruits/ha). The objective of the research was to determine the behavior of the agronomic and yield components under increasing dose of chicken in Cucumis melo L., var. "round gaucho melon", in Zungarococha-Loreto. 2021.The Statistical Design employed was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 2 rows, 5 plants/row, 3 seeds/stroke and the sampling unit consisted of 4 plants/experimental unit. experiment, the following conclusions were reached: The T4 Treatment (60 t henza/ha) presented the best agronomic characteristics and yield, with 5 fruits/plant, 16 cm of fruit length, 13 cm of fruit diameter, 2 mm of bark thickness, 1,248 g of fruit weight and 9,360 Kg of fruits/ha; in addition, it presented better profitability, with S/.18,738.00.